National trends in utilization and outcomes of elective open and minimally invasive colostomy reversal: A NSQIP analysis. - Kevin Tabibian; Nam Yong Cho; Oh Jin Kwon; Esteban Aguayo; Ayesha P Ng; Courtney Obasohan; Dariush Yalzadeh; Arjun Chaturvedi; Peyman Benharash; Hanjoo Lee (PLoS ONE)
Background Minimally invasive approach for reversal of Hartmann's procedure remains understudied. This study examined the outcomes associated with open and minimally invasive approaches for colostomy reversal in a national cohort. Methods The 2012-2022 American College of Surgeons National Surgical Quality Improvement Program participant use file data was queried to identify all adult (≥18 years) patients undergoing elective open or minimally invasive colostomy takedown. Multivariable regression models were developed to assess the associations between operative modalities and outcomes of interest, including overall complications (cardiac, respiratory, infectious, wound, renal and thromboembolic postoperative sequelae as well as reoperation and transfusion), operative duration, postoperative length of stay, and 30-day Readmissions. Results Among the 20,163 patients who underwent colostomy takedown during the study period, 6,180 (30.7%) had a minimally invasive reversal. Utilization of minimally invasive colostomy reversal increased from 18.2% in 2012 to 41.9% in 2022 (nptrend < 0.001). Following risk adjustment, minimally invasive colostomy takedown was associated with reduced odds of overall complications compared to the open approach (AOR 0.56, 95% CI 0.51-0.62). The minimally invasive approach was associated with decremental operative duration by 16.9 minutes (95% CI 13.6 to 20.2 minutes) and postoperative length of stay by 1.70 days (95% CI 1.56 to 1.84 days), as well as decreased odds of 30-day readmission (AOR 0.75, 95% CI 0.67-0.85). Conclusions Over the past decade, utilization of minimally invasive colostomy reversal has more than doubled and yielded lower overall complication rates compared to the open approach. Our findings suggest that the minimally invasive approach may be appropriate for colostomy takedown in suitable cases.